KANDUNGAN PENDIDIKAN KARAKTER DALAM POLA PENAMAAN MAHASISWA UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA KAMPUS KOTA MADIUN - Priska Meilasari; Agnes Adhani (Universitas Katolik Widya Mandala Surabaya, 2021)
The act of naming someone is not merely an act of giving someone’s name to call. It is an act of giving someone a remarkable notion that will be a reminder of what, where, or when someone was born. Besides, giving name is also an act of wishing and praying so the kids will be whatever their names are. Considering the wishes and hopes behind the act of naming, the researcher finds it interesting to analyze how parents’ give names to their children and what kind of wishes they implicitly asked for in those names. This study will use the semantic theory of meaning and the theory of character education. The data of the research are the 112 names of Widya Mandala Surabaya Catholic University Madiun Campus’ students. Those names are retrieved from Student Academic Biro of the University. The analysis shows that there are 5 character educational values found in those names.